Menelisik Ideologi Persatuan Kitab Arba’in Karya KH. Hasyim Asy’ari: : Sebuah Analisis Wacana Kritis - Hidayatullah, Alfin; Misbakhul Amin, Ahmad; Fadhil Febryansyah, Muhammad; Rijal, Syaiful; Ahmat Saepuloh (El Nubuwwah Jurnal Studi Hadis, 2025)
The rise of Islamic radicalism in post-reform Indonesia poses a serious challenge to national integration and religious harmony. Doctrines and movements grounded in exclusivism and intolerance toward religious diversity often trigger societal fragmentation. In this context, KH. Hasyim Asy'ari—founder of Nahdlatul Ulama—formulated an ideological response rooted in his compilation of ḥadīths entitled Arba‘īna Ḥadīthan Tata‘allaqu Bi Mabādi’ Jam‘iyyah Nahdlatil Ulama’. This study aims to examine the values of unity expressed through three core ḥadīths thematically linked to the concept of social cohesion, namely ḥadīth no. 16, 22, and 39. Employing a qualitative-descriptive method, the research adopts Teun A. van Dijk’s Critical Discourse Analysis framework, which incorporates macro-structure, schematic form, semantics, syntax, stylistics, rhetorical strategy, and social cognition. The findings reveal that while the isnād (chain of transmission) of the three ḥadīths varies—ranging from ḥasan li dhātihi, ṣaḥīḥ li dhātihi, to ḍa‘īf—their matn (textual content) is evaluated as ṣaḥīḥ based on compatibility with reason and foundational Islamic principles. The thematic values identified include empathy, solidarity, tolerance of difference, and the imperative to preserve communal harmony. This compilation of ḥadīths functions not merely as a religious text but also as an ideological manifesto responding to the socio-religious challenges of its time. In conclusion, Arba‘īna Ḥadīthan reflects a traditionalist yet progressive vision of Islam rooted in Ahl al-Sunnah wa al-Jamā‘ah, offering a normative framework for promoting moderation, pluralism, and national unity in contemporary Muslim societies.